2015
DOI: 10.1177/0954406215570105
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of influence of inlet guide vanes on unsteady flow in a centrifugal pump

Abstract: The influence of inlet guide vanes on unsteady flow in a centrifugal pump is numerically investigated. The independences of mesh elements, time steps and turbulence models are studied, and the satisfactory agreement between experimental and numerical results of the centrifugal pump performance validates the reliability and accuracy of the numerical model. The frequency characteristics of pressure fluctuations in impeller and volute are nearly the same for the pump without and with inlet guide vanes in the angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The steady calculation results were the initial condition for the unsteady calculation. The time step Dt = 2.2447 3 10 24 s, which is said to be accurate; [19][20][21] all 180 steps are in one rotating circle, calculating 15 circles in total, which is said to be accurate. 22 …”
Section: Computational Methods and Setupmentioning
confidence: 99%
“…The steady calculation results were the initial condition for the unsteady calculation. The time step Dt = 2.2447 3 10 24 s, which is said to be accurate; [19][20][21] all 180 steps are in one rotating circle, calculating 15 circles in total, which is said to be accurate. 22 …”
Section: Computational Methods and Setupmentioning
confidence: 99%
“…Tan et al [7] studied the effect of an adjustable inlet guide vane for the pre-swirl regulation of a single-stage centrifugal pump and obtained a higher efficiency and head at the design point at an angle of 24 • . Yuchuan et al [8] studied the same IGV for angles ±36 • and ±60 • to find the influence of guide vanes on unsteady flow. Qu et al [9] studied the clocking effect of the same IGV and found little influence on pump performance.…”
Section: Introductionmentioning
confidence: 99%
“…Early experimental and computational fluid dynamics (CFD) studies 4,6 showed that introducing preswirl increases the efficiency at lower mass flow rates and improves the surge limit. More recent studies have applied CFD simulations to investigate features such as performance, 7,8 unsteady interactions between the IGVs and the impellers, 9,10 pressure fluctuations at large IGV angles, 11 and the effect of IGV geometry. 1,12 A review of preswirl in from IGVs can be found in the work of Liu et al 13 Both experimental [14][15][16] and numerical 3,9,[17][18][19][20][21][22] approaches have been used to study compressor flow, with and without IGVs.…”
Section: Introductionmentioning
confidence: 99%